Carotenoids--4 : main lectures presented at the fourth International Symposium on Carotenoids, Berne, Switzerland, 25-29 August 1975 - Weedon, B. C. L. (Pergamon Press, 1976)
Carotenoids - 4 brings together the main lectures presented at the Fourth International Symposium on Carotenoids held in Berne, Switzerland, on August 25-29, 1975. The papers explore a wide range of topics relating to carotenoids, including their carbon-13 nuclear magnetic resonance (NMR) spectra, stereochemistry, and biosynthesis. Carotenoid-protein complexes, carotenoid glycosides, xanthoxin and abscisic acid, and photoregulation of carotenoid biosynthesis in plants are also discussed. This book is comprised of 13 chapters and begins with an analysis of the carbon-13 NMR spectra of derivativ.